Probabilistic analyses of soil consolidation by prefabricated vertical drains for single-drain and multi-drain systems - Bari, M.; Shahin, Mohamed; Soubra, A. (John Wiley & Sons Ltd., 2016)
Natural soils are one of the most inherently variables in the ground. Although the significance of inherent soil variability in relation to reliable predictions of consolidation rates of soil deposits has long been realized, there have been few studies that addressed the issue of soil variability for the problem of ground improvement by prefabricated vertical drains. Despite showing valuable insights into the impact of soil spatial variability on soil consolidation by prefabricated vertical drains, available stochastic works on this subject are based on a single-drain (or unit cell) analyses. However, how the idealized unit cell solution can be a supplement to the complex multi-drain systems for spatially variable soils has never been addressed in the literature. In this study, a rigorous stochastic finite elements modeling approach that allows the true nature of soil spatial variability to be considered in a reliable and quantifiable manner, both for the single-drain and multi-drain systems, is presented. The feasibility of performing an analysis based on the unit cell concept as compared with the multi-drain analysis is assessed in a probabilistic context. It is shown that with proper input statistics representative of a particular domain of interest, both the single-drain and multi-drain analyses yield almost identical results.